Comparison of rapid recovery outcomes between vNOTES hysterectomy and laparoscopic hysterectomy: a prospective study - Ying Tang; Chun-ling Fang; Jun-rong Huang; Xiao-mei Chen; Xin Cai; Jia Wu; Hui-quan Hu; Jun Li; Yue-xi Luo (BMC Surgery)
Abstract Background This study was aimed at evaluating the postoperative outcomes of vaginal natural orifice transluminal endoscopic hysterectomy (vNOTEH). Methods This prospective cohort study was conducted for comparing recovery outcomes, the time to first anal exhaust and return-to-work (RTW) time in vNOTEH versus laparoscopic hysterectomy (LH) groups. Linear regression analysis and cox proportional hazards regression were employed for analyzing the association between the recovery outcomes and surgical procedures. Results Altogether 330 patients were enrolled, with 92 in vNOTEH group whereas 238 in LH group according to the surgical procedure. Among them, 22 patients undergoing vNOTEH and 76 patients receiving LH returned to work. The operation time, the first anal exhaust time, RTW time, postoperative hospitalization of vNOTEH group remarkably decreased relative to LH group (P<0.05). Linear regression analysis indicated that the vNOTES approach was related to the time to first anal exhaust. Besides, Kaplan-Meier curve demonstrated the shorter median time to first anal exhaust in vNOTEH group than that in LH group (48.0 h vs. 69.0 h, P < 0.001). For patients who returned to work, multivariate Cox logistic regression revealed that surgical approach and postoperative hospitalization were significantly related to the RTW time. Furthermore, Kaplan-Meier curve showed that the median RTW time significantly decreased in vNOTEH subgroup relative to that in LH subgroup (2.0 months vs.3.0 months, P = 0.011). Conclusions and relevance vNOTES in women might be advantageous in the earlier recovery of intestinal function and the earlier return to work after hysterectomy compared with laparoscopy. Trial registration This study has been registered at https://www.chictr.org.cn with registration NO. ChiCTR2200063125 on Sep 27, 2022. The minimal postoperative follow up period was 1 month.